Metric characteristics of the modified step-hop test for assessing specific agility in young female volleyball players - Milic, M.; Grgantov, Z.; Stipkov, M. (Sport Science - International Scientific Journal of Kinesiology, 2016)
The aim of this study was to determine whether modification of the Step-hop test for assessing specific agility in volleyball would significantly shorten the performance time and improve homogeneity, i.e., reduce the differences between certain test items. The subject sample included 53 Croatian female volleyball players whose mean chronological age was 14.09±0.83 years, mean body height was 173.66±6.07 cm, and mean body mass was 61.12±9.40 kg. It was determined that the Modified Step-hop test had better reliability (CA=0.96 and CV=0.10) as compared to the Step-hop test (CA=0.93; CV=0.37). By simplifying performance, homogeneity of the test was improved (Step-hop F-test = 40.78; Modified Step-hop F-test = 10.76), and mean test performance time was shortened (Step-hop Mean = 10.75 sec; Modified Step-hop Mean = 9.78 sec). Even though correlation between the applied tests was significant (r=0.71), 50% of common explained variance points to somewhat different manifestations of agility required for performance of these tests. It can be assumed that the Step-hop test, due to unusual way of movement direction change, could also be applied to assess specific coordination, whereas the Modified Step-hop test has better metric characteristics for assessing specific agility in young female volleyball players.